The Phenomenon of Political Communication in the Era of Social Media Towards Public Polarization After the 2024 Presidential Election in Indonesia - Fata, Nuril Anwaril; Jannah, Siti Raudhatul; Wazis, Kun (SAINTIS Publishing, 2025)
This research examines the impact of social media on political communication and public polarization. Social media, initially designed to foster social interactions, has become a political arena, leading to conflicts of interest through controversial campaign content for the 2024 presidential election. The study focuses on the emergence of public division into camps supporting each candidate, such as Anis-Muhaimin, Prabowo-Gibran, and Ganjar-Mahfud. Each candidate has different narrative content themes, such as change movements, Jokowi's program, and Indonesia's excellence. This unique phenomenon continues until the inauguration of the elected president. Tensions between the losing and winning camps continue on social media timelines. The research uses a netnographic method with a qualitative approach. Social media enables rapid and extensive political communication, but concerns have arisen about ethical communication violations committed by its users. Content displayed by candidates or their success teams can create an echo chamber, reinforcing voters' views. The emergence of consultants, influencers, and political buzzers further exacerbates this issue, fostering division among societal groups.